IoT device management framework for smart home scenarios - Perumal, Thinagaran; Datta, Soumya Kanti; Bonnet, Christian (IEEE, 2015)
The paradigm of the Internet of Things (IoT) requires pervasive connectivity to billions of heterogeneous devices. In recent time, rapid growth of IoT devices in smart home environment envisioned a wide range of novel services and applications. However, due to the inherent heterogeneity, home environment is becoming complex making device management extremely difficult. This paper proposes a lightweight IoT device management framework for smart home services. The framework can be deployed at home gateways and consumer smart devices. A prototype implementation and performance evaluation results are also presented.